Central Nervous System Demyelination in a Charcot-Marie-Tooth Type 1A Patient - Christos Koros; Maria-Eleftheria Evangelopoulos; Costas Kilidireas; Elisabeth Andreadou (Case Reports in Neurological Medicine)
Introduction. Central nervous system involvement, either clinical or subclinical, has been reported mainly in X-linked Charcot-Marie-Tooth (CMT-X) patients. Case Presentation. We present the case of a 31-year-old man with a genetically confirmed history of CMT1A who developed CNS involvement mimicking multiple sclerosis (MS). Clinical, imaging, and laboratory findings suggested an autoimmune CNS demyelination. Discussion. Although the simultaneous existence of CMT1A and MS could be coincidental we postulate that overexpression of PMP22, the target protein in CMT1A, might influence the immunological self-tolerance to CNS proteins via molecular mimicry, leading to a CNS autoimmune demyelinating disorder.